2019
DOI: 10.1186/s13068-018-1332-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fatty Acid EXporters involved in fatty acid transport for oil accumulation in the green alga Chlamydomonas reinhardtii

Abstract: BackgroundIn the past few decades, microalgae biofuel has become one of the most interesting sources of renewable energy. However, the higher cost of microalgae biofuel compared to that of petroleum prevented microalgae biofuel production. Therefore, the research on increasing lipid productivity from microalgae becomes more important. The lipid production source, triacylglycerol biosynthesis in microalgae requires short chain fatty acids as substrates, which are synthesized in chloroplasts. However, the transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 36 publications
(60 reference statements)
3
40
1
Order By: Relevance
“…and DsMEK1-X2 gene were performed in those lines, which confirmed that the related genes were overexpressed or knock down ( Fig. 5C) [35].…”
Section: Dsmek1 Is Regulated By Alternative Splicingsupporting
confidence: 64%
“…and DsMEK1-X2 gene were performed in those lines, which confirmed that the related genes were overexpressed or knock down ( Fig. 5C) [35].…”
Section: Dsmek1 Is Regulated By Alternative Splicingsupporting
confidence: 64%
“…Thus, to use algae as an efficient alternative energy source for biodiesel production, the challenge remains to increase both lipid productivity and biomass concentration. Meanwhile, there have been other efforts to increase biomass production as well as the lipid content of a microalgae through various genomic and proteomic approaches that will uncover the biological implications and pave the future tailored manipulation of microalgae for broader industrial applications (Anand et al 2017;Banerjee et al 2017;Li et al 2019). However, for any kind of modifications to be made at the molecular level, the first step is to screen microalgae strains from different habitats and examine them for their inherent properties to be used as an ideal strain for biodiesel production (Jagadevan et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…qRT-PCR assays of the DsMEK1-X1 and DsMEK1-X2 genes were performed in those lines, which confirmed that the related genes were overexpressed or knockdown ( Fig. 5c) [28].…”
Section: Dsmek1 Is Regulated By Alternative Splicingmentioning
confidence: 56%